2022
DOI: 10.5755/j02.ms.29008
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of GRC-SWCNT Composites for Shell Elements

Abstract: Nano-sized defects in Glass fiber Reinforced Concrete (GRC) shell elements can cause damage over time, leading to mechanical and durability problems. Therefore, in this study an experimental program was conducted to investigate the application of single-walled carbon nanotube as a nano-additive material in GRC. Since there is no study on GRC-carbon nanotube (CNT) composites in the literature, the behavior of CNTs on conventional concretes was discussed. Five different GRC-SWCNT composite mixtures containing 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, since the aim of this study was to design a conductive mortar mix, the SWCNT ratio was kept above the literature, which may decrease the strength by causing low adherence between the filler and the binder in the mixture. Studies [31,46], have reported improvements in the strength of cementitious materials using lower dosages of SWCNT.…”
Section: Mechanical Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, since the aim of this study was to design a conductive mortar mix, the SWCNT ratio was kept above the literature, which may decrease the strength by causing low adherence between the filler and the binder in the mixture. Studies [31,46], have reported improvements in the strength of cementitious materials using lower dosages of SWCNT.…”
Section: Mechanical Test Resultsmentioning
confidence: 99%
“…As a pozzolanic additive material, calcined kaolin was preferred in equal proportions in all mixtures. Previous studies have shown that calcined kaolin performs well when used with white cement [30,31]. The particle size ranges of silica sand, cement and calcined kaolin were compared in Table 1.…”
Section: Materials Propertiesmentioning
confidence: 99%